GROUP OF SUOI BA ARCHAEOLOGICAL SITES (DAK NONG PROVINCE): DOCUMENTS, PERCEPTION, AND DISCUSSION - Thanh Vuong Nguyen; Xuan Hung Le; Trong Tue Cao; Thi Dung Hoang; Anh Bien Hoang (Tạp chí Khoa học Đại học Đà Lạt)
This article introduces the results of investigations and surveys from 2006 to 2017 of the group of Suoi Ba archaeological sites in Nhan Co commune, Dak R’Lap district (Dak Nong). The results reveal eight prehistoric archaeological sites in the Suoi Ba area, which are distributed over an area of about 20 hectares, equivalent to the size of an ancient village, and date from 3,500 to 2,000 years BP. In this study, the authors systematize materials, assess historical-cultural values, briefly outline the prehistoric cultural process at Suoi Ba during the late Neolithic and early Metal Age in Dak Nong, and discuss issues related to Suoi Ba relics in a broader context.